(untitled) (GnosisWisdom, 2022)
This research stems from the concern to explore the socio-spatial dynamics of street dwellers, categorized as "indigent" in order to understand and understand how it is based through the ways of living, living, thinking and acting, the public spaces that are immersed in the middle of the historic center of the city of Santa Marta and that in turn are objects of resignification by these same people. This article intends to analyze said configuration and resignification of these public spaces, by the inhabitants of the street, in the same way to account for the social and spatial dynamics that arise from the inhabiting of the inhabitants of the street. During the investigation, a series of concepts will be touched upon that will allow a methodological understanding of this reality of the city, such concepts as space, public space, heterotopia, location, homelessness, social exclusion and marginality, where a gear focused on the anthropology of space will be developed. and urban anthropology.